Back Cover: Discovery of a PCAF Bromodomain Chemical Probe (Angew. Chem. Int. Ed. 3/2017). Issue 3 (23rd December 2016) - Moustakim, Moses; Clark, Peter G. K.; Trulli, Laura; Fuentes de Arriba, Angel L.; Ehebauer, Matthias T.; Chaikuad, Apirat; Murphy, Emma J.; Mendez‐Johnson, Jacqui; Daniels, Danette; Hou, Chun‐Feng D.; Lin, Yu‐Hui; Walker, John R.; et al.
Abstract : Epigenetic drug discovery has now witnessed the emergence of a new target class of proteins, the bromodomains. In their Communication on page 827 ff., D. J. Dixon, P. E. Brennan et al. report the first potent, selective, cell‐permeable, and cell‐active chemical probe for the p300/CBP associated factor (PCAF) bromodomain. A combination of computational docking studies, inhibitor design, and asymmetric synthesis furnished their probe, L ‐Moses, for use as a chemical tool for this epigenetic target to interrogate its role in associated diseases.